Social Media as a Strategic Marketing Communication Tool in Palestinian Mobile Telecom Companies - Business to Customers Relationship Perspective - Diebes, Hala M.Y.; Iriqat, Raed A.M. (International Review of Management and Marketing, 2019)
The aim of the research is to identifying the role of social media in building customer relationships; the study also aims at using social media as a strategic marketing tool for telecom companies. The researcher used Jawwal as a case study in the aspect of: (brand awareness, knowledge of services and products, and intention to purchase).Through a quantitative approach by designing a survey questionnaire as a tool of collecting data. The sample included (432) of Jawwal Customer's Mobile Telecom Company in Palestine that used different social media platforms. Results showed that social media affect building customer relationship and its elements: (Brand awareness, knowledge, and intention to buy). The most important recommendation of this research is: To utilize the use of social media in marketing communication mixes strategies for telecom mobile companies, because they have a major role and influence in building customer relationships. Keywords: Social Media, B2C-Relationsip, Brand Awareness, Knowledge and Purchase Intention. JEL Classifications: M300, M310 DOI: https://doi.org/10.32479/irmm.7714